In Memoriam: Professor Dr Vincentas Rolandas Giedraitis (1972-2025) - Stavytskyy, Andriy; Bartkus, Algirdas; Stankevičienė, Jelena (Ekonomika, 2025)
This tribute, penned in the shadow of profound loss, honors the life and legacy of Prof. Dr Vincentas Rolandas Giedraitis, a luminary in economic history, socioeconomics, and criminology whose rigorous scholarship illuminated the turbulent waters of emerging markets. Vincentas Rolandas Giedraitis was a prominent Lithuanian economist whose academic legacy reflects substantial contributions to empirical economics, sustainability, and interdisciplinary policy research. With a strong citation record and publications in leading international journals, his research addressed key issues such as maternal health, energy consumption, economic development, and environmental sustainability. His work applied rigorous econometric and statistical methods to examine socioeconomic inequalities, energy security, and institutional transformation, particularly in Central and Eastern Europe and developing regions. Beyond research, prof. V. R. Giedraitis played a pivotal role in advancing academic publishing and international collaboration. At Vilnius University, he strengthened doctoral training, mentored young scholars, and led interdisciplinary initiatives. His editorial leadership enhanced the international visibility of economic journals and fostered partnerships with institutions such as Taras Shevchenko National University of Kyiv. His legacy endures through his scholarly contributions, institutional leadership, and lasting influence on economic research and academic communities.